20 Adolescent and caregiver perspectives on living with a limb fracture: A qualitative study. (29th October 2021) - Bharadia, Manisha; Golden-Plotnik, Stevi; van Manen, Michael; Sivakumar, Mithra; Drendel, Amy; Poonai, Naveen; Moir, Mackenzie; Ali, Samina
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: Fractures occur in up to half of children by age 16 years. After initial emergency care for a fracture, function is universally impaired in children, and impacts extend to the immediate family. Knowledge of expected functional limitations is key to providing proper discharge instructions and anticipatory guidance to families. Objectives: Our study objectives were to understand: 1) how adolescents (12-17 years) describe the functional impact of fractures on their lives; 2) how adolescents' reports of their experiences compare to those of their caregivers; and 3) the impact of the fracture on the family unit. Design/Methods: We conducted individual, semi-structured interviews from June 2019 to November 2020 with adolescents and their caregivers, 7-14 days following their initial visit to a pediatric emergency department. We utilized qualitative content analysis methodology. Recruitment proceeded until thematic saturation was achieved. Coding and analysis were concurrent with recruitment and interviews. A secondary coder reviewed 40% of the transcripts, and the coding team met regularly to discuss the coding framework and key themes. The interview script was modified in an iterative process, to reflect emerging themes. Results: We completed a total of 29 interviews. The most commonly affected functions were: a) showering and hygiene (which required the most caregiver support); b) sleep variability (due to pain and cast-related discomfort); and c) exclusion from sports/activities. Many adolescents experienced disruptions to social activities and gatherings. Adolescents valued independence and often chose to take more time to complete a task to preserve this, regardless of inconvenience. Both adolescents and caregivers reported feelings of frustration as a result of day-to-day impacts imposed by the injury. Generally, caregivers' perspectives were in keeping with the experiences that adolescents described for themselves. Notable family impacts included what we described as 'sibling burden' or conflicts that arose when a sibling had to take on extra chores/tasks. Conclusion: These themes highlight an opportunity to better tailor discharge instructions for adolescents with fractures. Key messages include: 1) expect pain and impaired sleep, especially in the first few days; 2) allow extra time to complete tasks independently, especially for grooming and hygiene; 3) consider family impact, especially sibling burden; 4) prepare for changes in activities and social dynamics; and 5) frustration is normal, for both adolescents and caregivers. Future work can focus on developing a novel, family-informed tool to assess functional outcomes following injury.